Social Influence in the Public Expression of LGBTQ+ Support: The Case of Rainbow Flags in Residential Neighborhoods of a European City - Dominic Amstutz; Jaemin Lee (Socius)
With the growing acceptance of diverse sexual orientations, displaying rainbow flags has become a widespread urban practice, symbolizing solidarity with the LGBTQ+ community. What motivates individuals to publicly express support for the rights of sexual minorities beyond private approval? The authors explore whether social exposure among flat neighbors contributes to the public display of rainbow flags on private windows and balconies by conducting an extensive field observation of 135,202 residents in the city of Bern, Switzerland. The authors applied models to compare the spatial clustering of flagged households with a simulated distribution representing independent actors at façades, a granular approach to address residential self-selection. The analysis reveals that flagged households are significantly closer to one another on façades than expected under random conditions, indicating social influence among close flat neighbors. The authors also observed an excess of buildings either completely devoid of flags or displaying a large number of them, suggesting that committed minorities can induce a self-reinforcing cycle whereby each nearby flag lowers perceived risks for nonadopters, increasing the likelihood of further displays. These results suggest that the public expression of LGBTQ+ support not only stems from individual beliefs but also can emerge through social exposure to neighboring supporters.